In vitro Anti-MDR Bacteria, Anti-inflammatory and Antioxidant Activities of Ceratonia siliqua L. - Shuaib, Mustafa; Kabbashi, Ahmed; Eltawaty, Salwa; Ismail, Amar (AlQalam Journal of Medical and Applied Sciences, 2025)
The present study demonstrated the in vitro antibacterial activity against multidrug-resistant (MDR) isolates, as well as the anti-inflammatory and antioxidant effects of the Ceratonia siliqua L. (C. siliqua) ethanolic extract from Al-Bayda City, located in the Green Mountain. The C. siliqua fruit extract was obtained using 75% ethanol. The agar-well diffusion method investigated the antibacterial activity against MDR isolates. The albumin denaturation method was employed to demonstrate the anti-inflammatory activity, and the antioxidant activity of the extract was evaluated using DPPH scavenging activity. The extract showed promising antibacterial activity against MDR isolates, with higher inhibition zones against S. aureus, followed by Ps. aeruginosa, K. pneumoniae, and E. coli. The extract showed high inhibitory activity against albumin denaturation, with an IC50 of 368.5 µg/ml. Moreover, the DPPH scavenging method revealed a weaker antioxidant activity of the C. siliqua extract (42.86 ± 0.08 %) at a concentration of 500 µg/ml compared with the control. In summary, the fruit C. siliqua ethanolic extract is a promising therapeutic agent for MDR isolates and has the potential to reduce inflammation and oxidative stress.